A Formal Palliative Care Service Improves the Quality of Care in Patients with Stage IV Cancer and Bowel Obstruction. (February 2017) - Gabriel, Emmanuel; Kukar, Moshim; Groman, Adrienne; Alvarez-Perez, Amy; Schneider, Jaclyn; Francescutti, Valerie
Background: Patients with stage IV cancer and bowel obstruction present a complicated management problem. The aim of this study was to evaluate the role of the palliative care service (PC) in the management of this complex disease process. Methods: A retrospective analysis was conducted of all patients admitted to Roswell Park Cancer Institute with stage IV cancer and bowel obstruction from 2009 to 2012 after the institution of a formal PC. This cohort was matched to similar patients from 2005 to 2008 (no palliative care service or NPC). Patient characteristics and outcomes included baseline demographics, comorbid conditions, do-not-resuscitate (DNR) status, laboratory parameters, medical and surgical management, length of stay, symptom relief, and disposition status. Results: A total of 19 patients were identified in the PC group. Based on the PC group baseline characteristics, 19 patients were identified for the NPC group using matched values. Regarding outcomes, there were significant differences in the medication regimens (narcotics, octreotide, and Decadron) between the 2 groups. In the PC group, 14 of 19 patients showed improvement compared to 9 of 19 in the NPC group. Nearly 60% of patients in the PC group had a formal DNR order versus 10.5% in NPC ( P = .002). A significantly higher percentage of patients were discharged to hospice in the PC group (47.4% vs 0.0%, P = .006). Conclusion: Palliative care consultation improves the quality of care for patients with stage IV cancer and bowel obstruction, with particular benefits in symptom management, end-of-life discussion, and disposition to hospice.